Paul of Dune - Herbert, Brian (Tor, 2009)
Frank Herbert's Dune ended with Paul Muad'Dib in control of the planet Dune. Herbert's next Dune book, Dune Messiah, picked up the story several years later after Paul's armies had conquered the galaxy. But what happened between Dune and Dune Messiah? How did Paul create his empire and become the Messiah? Following in the footsteps of Frank Herbert, New York Times bestselling authors Brian Herbert and Kevin J. Anderson are answering these questions in Paul of Dune.